2009
DOI: 10.1242/jcs.055996
|View full text |Cite
|
Sign up to set email alerts
|

The integrin adhesion complex changes its composition and function during morphogenesis of an epithelium

Abstract: Cell adhesion to the extracellular matrix (ECM) is mediated by the integrin family of transmembrane receptors. Integrins link ECM ligands to the cytoskeleton, providing strong attachment to enable cell-shape change and tissue integrity. This connection is made possible by an intracellular complex of proteins, which links to actin filaments and controls signalling cascades that regulate cytoskeletal rearrangements. We have identified stress-fibre-associated focal adhesions that change their composition during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 72 publications
5
94
0
8
Order By: Relevance
“…In stage 11, they rapidly become squamous, doubling their apical and basal areas and trebling their perimeters in 20 min. Whereas external forces drive this squamous expansion as nurse cells empty their contents into the oocyte, the FCs must nevertheless actively remodel their junctions and membrane domains to maintain adhesion to the extracellular matrix (Delon and Brown, 2009;Schotman et al, 2008), cell-cell adhesion (Pope and Harris, 2008) and epithelial integrity. Because optical constraints make it difficult to image squamous cells in cross-section, we employed maximal projections encompassing the apical junctions and apical surface (see Materials and Methods and supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In stage 11, they rapidly become squamous, doubling their apical and basal areas and trebling their perimeters in 20 min. Whereas external forces drive this squamous expansion as nurse cells empty their contents into the oocyte, the FCs must nevertheless actively remodel their junctions and membrane domains to maintain adhesion to the extracellular matrix (Delon and Brown, 2009;Schotman et al, 2008), cell-cell adhesion (Pope and Harris, 2008) and epithelial integrity. Because optical constraints make it difficult to image squamous cells in cross-section, we employed maximal projections encompassing the apical junctions and apical surface (see Materials and Methods and supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, this cannot be a universal mechanism, as other sites of integrin adhesion lack Wech (Delon and Brown, 2009). Studies in vertebrate cells have identified additional ILK interactions that provide alternative mechanisms to link ILK to talin.…”
Section: Regions Of Ilk Required For Localization At Massmentioning
confidence: 99%
“…This idea is supported by previous work showing that a mutant bPS chimera that cannot transduce tension (comprising the cytoplasmic tail fused to an extracellular domain that cannot bind ECM ligands) can recruit talin but not PINCH or tensin . In addition, a recent Drosophila study illustrates that force may be required for the recruitment of IAC components, as the extracellular domain of aPS2-integrin is required for intracellular tensin recruitment in ovarian epithelial cells (Delon and Brown, 2009). Thus, force may play crucial roles in recruiting certain IAC components during tissue morphogenesis.…”
Section: Pines Et Almentioning
confidence: 99%